Communicative Strategies and Tactics of Trolls-Aggressors in Computer-Mediated Communication during COVID-19 Pandemic - O. Yu. Gukosyants; O. A. Alimuradov; Z. U. Khakiyeva (Научный диалог)
The article considers the aggressive communicative behaviour of a virtual linguistic personality provoking a communication conflict in the virtual space (a troll-aggressor). The data include comments retrieved from LiveJournal posts and Internet memes published during the COVID-19 pandemic. In the course of the analysis, the authors reveal the communicative roles, strategies and tactics of trolls-aggressors. The common strategy of the troll’s aggressive conflict interaction in the indicated time period is the strategy of hostility which is embodied in particular strategies (micro-strategies) of discrediting and attack. It is concluded that discrediting as a micro-strategy can be implemented via a false compliment, the tactic of taunt, the tactic of insult and the tactic of blaming. The micro-strategy of attack is implemented by means of threat and indignation. Particular attention is paid to the description of the markers of the above-listed tactics observed in trolls-aggressors’ communicative behaviour. Enumeration of the tactics used for provoking conflicts in virtual environment made it possible to concretize the typology of trolls-aggressors which has been revealed in the course of empiric data analysis. As a result, the authors present a scheme which reflects the types of trolls, belonging to the general type “troll-aggressor”, and the implemented communicative strategies and tactics within the framework of the common strategy of hostility.